A Statistical Inversion Approach for Local Thermal Diffusivity and Heat Flux Simultaneous Estimation - Sepulveda-Palma, F (Taylor and Francis Ltd., 2014)
The mapping of thermophysical properties from thermal images provided by an infrared camera is a difficult inverse problem, due to the large amount of data to be processed, large number of parameters to be estimated and low signal-to-noise ratio. It is thus of great interest to implement estimation approaches of low computational cost that can accurately cope with such inherent difficulties. In this paper, we make use of the so-called statistical inversion approach for the solution of an inverse problem that involves the identification of both local thermal diffusivity and local heat flux. Experimental results are presented for two kinds of heating: front face heating with a laser diode and back surface heating with an electrical resistance. © 2014 Taylor & Francis.